Turbulence modeling and simulation advances in CFD during the past 50 years - Schiestel, Roland; Chaouat, Bruno (Comptes Rendus. Mécanique)
This paper is a short retrospective review of the predictive methods of turbulent flows in Computational Fluid Dynamics over the last 50 years since the first development of computers. The different schools of turbulence modeling are presented with the aim to guide both users and researchers involved in numerical simulation of turbulent flows.